Air Circulation Improvement through Exhaust and Fan Installation: Peningkatan Sirkulasi Udara Melalui Pemasangan Exhaust dan Kipas - Fawwaz , Muhammad Rafly; Tjahjanti, Prantasi Harmi (Procedia of Engineering and Life Science, 2025)
Technological advances in the transportation sector are currently increasing rapidly, especially in this advanced era. Indonesia has a human population of 273.5 million. It is not surprising that Indonesia is the 15th largest country in the world. There are several options for air circulation in a room, depending on what kind of room you are in. The spaces in the building have a connection between spaces which is called circulation. Circulation is also a movement path which can be said to be a thread or rope which has the aim of connecting spaces within a building and also connecting indoor and outdoor spaces. Circulation also becomes a place for someone to feel a space through that person's origin and destination. In a building, circulation is a positive element that can influence a person's perception of the shape and space in the building.